THE RELATIONSHIP OF FAMILY SUPPORT TO THE ELDERLY DEPRESSION LEVEL IN POSYANDU ELDERLY AT SIWALAN, WIDODAREN VILLAGE, GERIH DISTRICT, NGAWI REGENCY - Viki, Ariyanti; Kurniawan, Vendi Eko; Aziz, Aditya Nuraminudin (LPPM STIKes Bahrul Ulum Jombang, 2019)
Depression is a period of disruption of human functions related to the nature of the sad feelings and symptoms of the invaders. Family support is a therapy form that includes depression management in the elderly. The purpose of this research is to know the relationship of family support to the level of depression in the elderly. The design of this research is correlational analytic with cross sectional approach with a population of all elderly with age 50-70 years in Posyandu elderly at Siwalan Widodaren Village Gerih District of Ngawi Regency which samples used numbering 81 respondents using the purposive sampling technique. This research data uses the questioners of family support and depression GDS-15, in reality, the results more than half of the support provided by the family enough or moderate as much as 54.3% and a large age of elderly depression suffered as much 67.9%. Finally, the result is 0.000 which means 0.000 < 0.05, then HI acceptable means there is a significant relationship between family support to the level of elderly depression. Then tabulation of the data using the correlation test Spearman Rank. The families should be able to provide support and attention to the elderly so that they feel and still needed and not regarded as a burden, so that the incidence of depression can be minimized. Keywords: family support, elderly and depression levels